The relationship between ethnicity and service access, treatment uptake and the incidence of psychosis among people at ultra high risk for psychosis. (February 2019) - Byrne, Majella; Codjoe, Louisa; Morgan, Craig; Stahl, Daniel; Day, Fern; Fearon, Paul; Fusar-Poli, Paolo; Power, Paddy; McGuire, Philip; Valmaggia, Lucia
Highlights: Black minority ethnicity was overrepresented in young people at ultra high risk for psychosis. There were no differences between ethnic groups in rates of transition to psychosis. Delivering treatment at the at risk for psychosis stage might provide a means of reducing the differences in the incidence of psychosis between ethnic groups, although this would need to be replicated in a larger sample. Ethnicity did not impact on the type of treatments accessed. Abstract: Black ethnicity is associated with increased risk for psychosis in South London. This study explored the distribution of ethnicity among services users at ultra high risk for psychosis (UHR) and examined the influence of ethnicity on service access, treatment uptake and incidence of psychosis. The ethnic distribution of 228 people at UHR for psychosis, seen in an early detection clinical service over 10 years, was compared with 146 people with first episode psychosis from the same geographic region and census figures for the local population. Black service users were significantly over-represented in the UHR group compared to the background population (34% vs 21%; p  < 0.05); but less so than in the first episode sample (58% vs 19%; p  < 0.05). Within the UHR sample, there was no strong evidence of differences between ethnic groups in the types of treatment provided, nor in the rate of transition to psychosis over 2 years. The absence of differences between ethnic groups in rates of transition to psychosis raises the possibility that access to mental health care at the high risk stage might have reduced the influence of ethnicity on the incidence of psychosis in this sample. This would need to be replicated in a larger sample.